Comparing the Institution-based Supervision and Tele-based Supervision for Task-oriented Exercises on Upper Limb Motor Performance and Functional Ability among Stroke Patients: A Research Protocol - Neha; Subhasish Chatterjee (Journal of Clinical and Diagnostic Research)
Introduction: Rehabilitation is a vital part of recovery for stroke patients, presenting a complex intervention that requires collaboration among patients, caregivers and the rehabilitation team. Telerehabilitation has emerged as a promising alternative to standard outpatient and home-care rehabilitation, offering advantages such as minimal travel barriers, flexible exercise schedules and the integration of skills into daily activities. Need of the study: The technologies that can be used for telerehabilitation range from inexpensive internet-based solutions, virtual reality, and robotic systems to more costly telephones and mobile phones, which are present in most homes. Physiotherapists have been suggested as being in the best position to help stroke victims transition from the hospital to their homes. However, there has been significant international professional resistance to using telerehabilitation-based services, based on the belief that the lack of in-person care may result in worse outcomes. Nevertheless, research on numerous chronic health disorders demonstrates that telerehabilitation strategies can effectively enhance results. There is a dearth of literature comparing tele-based supervision for task-oriented exercises with institution-based supervision for task-oriented exercises. Thus, the need for this study is to identify a cost-effective method for rehabilitation in stroke patients. Aim: To compare the effect of institution-based supervision and tele-based supervision for task-oriented exercises on upper limb motor performance and functional ability among stroke patients. Materials and Methods: A two-group pretest-post-test randomised clinical trial will be conducted in recognised hospitals in Mullana and Panipat, using purposive sampling from December 2022 to December 2024. A total of 62 male and female patients, aged 45-75 years, who have experienced their first ischaemic or haemorrhagic stroke within the last six months and have scores ranging from 26 to 56 on the Fugl-Meyer Assessment for Upper Extremity (FMA-UE), mild to moderate spasticity (less than 2 on the Modified Ashworth Scale (MAS), >24 on the Mini-mental State Examination (MMSE), and stages II and III of the Brunnstrom score will be included in the study. Group B will receive institution-based supervision for task-oriented exercises, whereas Group A will receive tele-based supervision for live sessions. Both groups will perform task-oriented exercises for 30 minutes, three days a week for eight weeks. There will be a 30-second break before switching tasks. Outcome measures, including the Fugl-Meyer Assessment for Upper Extremity (FMA UE) and the Motor Evaluation Scale for Upper Extremity in Stroke Patients (MESUPES), will be assessed at baseline, the 4th week, and the 8th week of intervention, respectively. Repeated measures of Analysis of Variance (ANOVA) or the Friedman test will be chosen based on normality to find differences within the groups at baseline, the 4th week, and the 8th week (completion). A paired t-test or Wilcoxon signed-rank test will be applied to identify differences between the groups for pre-post intervention changes in outcome measures. An Independent t-test or Mann-Whitney U-test will be applied based on normality to compare the changes in mean values of the outcome measures between Group A and Group B at baseline, the 4th week, and the 8th week of intervention. The level of statistical significance will be set at alpha=0.05.